Heavy metal contamination of soil-derived interstitial water in the coastal regions of Selangor, Malaysia - P, Agamuthu, (Malaysian Journal of Science, 2001)
Soil-derived interstitial water from five sites along the industrially active West Coast of Peninsular Malaysia was investigated for heavy metal contamination. The five sites are (i) near Port Klang, (ii) near a toll plaza, (iii) Sg. Lang, (iv) landfill site near Sabak Bernam and (v) Teluk lntan town center. The concentrations of the heavy metals studied (Fe, Mn, Pb, Zn, Cu and Cd) were, in general, above the permissible limit for Domestic Water Supply and therefore requires treatment before the water is used for domestic consumption. Lateral and vertical movement of groundwater and landfill leachate (at least in the case of Sabak Bernam landfill) probably influenced the heavy metal content and distribution in the soil. Soil contamination in and around Teluk lntan was by industrial effluent whereas the landfill in Sabak Bernam was also a contributory factor there. Since 99% of the municipal waste dumps in Malaysia do not use a liner system, this investigation further reinforced the need for incorporating such a system in all future landfill developments.